2016
DOI: 10.1073/pnas.1518934113
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of HCV virions reveals an essential role for the nucleoporin Nup98 in virus morphogenesis

Abstract: Hepatitis C virus (HCV) is a unique enveloped virus that assembles as a hybrid lipoviral particle by tightly interacting with host lipoproteins. As a result, HCV virions display a characteristic low buoyant density and a deceiving coat, with host-derived apolipoproteins masking viral epitopes. We previously described methods to produce high-titer preparations of HCV particles with tagged envelope glycoproteins that enabled ultrastructural analysis of affinity-purified virions. Here, we performed proteomics stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 22 publications
4
58
0
1
Order By: Relevance
“…The highly infectious purified particles have a diameter of 81 to 85 nm and display a complex internal structure (18). A proteomic analysis of cellular proteins associated with HCV virions purified by using neutralizing antibody AR3A showed that ApoE, ApoB-100, ApoA-II, ApoC-II, and ApoC-III are associated with purified HCV virions (48). Overall, these findings strongly support the notion that HCV virions are assembled and secreted as LVPs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The highly infectious purified particles have a diameter of 81 to 85 nm and display a complex internal structure (18). A proteomic analysis of cellular proteins associated with HCV virions purified by using neutralizing antibody AR3A showed that ApoE, ApoB-100, ApoA-II, ApoC-II, and ApoC-III are associated with purified HCV virions (48). Overall, these findings strongly support the notion that HCV virions are assembled and secreted as LVPs.…”
Section: Discussionsupporting
confidence: 53%
“…The interaction of the HCV envelope glycoproteins E1 and E2 with ApoB and ApoE at the ER hints that the glycoproteinapolipoprotein complex could initiate the formation of hybrid lipoviroparticles (50). The presence of ApoB, along with other exchangeable apolipoproteins such as ApoE, ApoA-II, ApoC-II, and ApoC-III, on HCV virions emphasizes its role in HCV maturation and egress (18,48). In correlation, immunogold electron microscopy clearly indicated the presence of ApoB, although in small amounts, and ApoE along with the HCV structural proteins in COPII vesicles, suggesting that the viral particles that bud from the ER are associated with ApoB and ApoE (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear basket nucleoporin Nup153, which plays direct roles in importin alpha/beta mediated protein import [96], binds to the HIV capsid and knockdown of this nucleoporin reduces capsid entry [97]. In a proteomic analysis of HCV capsid interacting proteins, Nup98 was identified as critical for HCV entry into the nucleus and the subsequent propagation of the virus [98]. A nucleoporin found on both faces of the NPC, hCG1 [99], binds to the HIV protein Vpr and this interaction aids in the nuclear import of the viral protein [100].…”
Section: Npcs In Viral Infections and Immunitymentioning
confidence: 99%
“…Knock down HCVcc is the corresponding polymerase-defective mutant that inhibits viral replication. Viral stocks were prepared using electroporation on Huh 7.5 cells as described [14]. Infectious titers of HCVcc inocula were determined using Huh 7.5 cells as described.…”
Section: Gluc Hcvcc Infection and Analysismentioning
confidence: 99%